Potensi Pengambangan Sentra Peternakan Kambing Etawa Desa Bangelan, Kecamatan Wonosari, Kabupaten Malang (Fakultas Teknik, Universitas Brawijaya, 2024)
This service activity aims to unlock the potential and development opportunities of Bangelan Village, one of which is Goat Farming. The majority of people's livelihoods are farming and animal husbandry. Almost all the people in Bangelan Village have around 20 goats. One of the livestock groups in Bangelan Village is the Karya Mulya Livestock Group. However, they face obstacles in the form of feed and livestock pens that are not used optimally. Forage is difficult to find, especially in the dry season, so it is necessary to stock food so that farmers do not have difficulty finding feed in the dry season. The cage used is also a traditional cage that has been passed down from our ancestors. The methods applied in this service activity include tracing and interviews with the Karya Mulya Community and Livestock Group. The final results show several plans that will be carried out to resolve existing problems. In conclusion, the Karya Mulya livestock group in Bangelan Village was successful in determining a way to resolve the livestock problem.